ANALYZING THE IMPACT OF TOURISM DEVELOPMENT ON URBAN SPATIAL STRUCTURE AND LAND USE CHANGE - Panji Indarta Pratama (Adisam Publisher, 2026)
The expansion of the tourism industry has become a significant driver of urban development, particularly by influencing urban spatial structure and land-use patterns. The growing number of tourist arrivals stimulates investment, infrastructure development, and the provision of supporting facilities, thereby accelerating urban spatial transformation. Nevertheless, this rapid growth may also generate several challenges, including land-use conversion, increasing development density, traffic congestion, and environmental degradation when not supported by sustainable spatial planning policies. This study aims to examine the impacts of tourism development on changes in urban spatial structure and land utilization by synthesizing established theories and findings from previous studies. A descriptive qualitative approach was employed using a literature review method. The study relied exclusively on secondary data collected from national and international scientific journals, academic books, government policy documents, reports published by international organizations, and other relevant scholarly publications. The data were analyzed using content analysis, involving the processes of identification, classification, interpretation, and synthesis of the selected literature. The findings indicate that tourism development contributes to the emergence of new economic growth centers, intensifies urban land utilization, and encourages the conversion of residential areas and open spaces into commercial and tourism-related service zones. While tourism expansion generates positive outcomes, including increased investment, employment opportunities, regional economic growth, and improved infrastructure, it also produces adverse impacts such as uncontrolled land conversion, greater environmental pressure, traffic congestion, and the reduction of urban green open spaces. Therefore, tourism development should be integrated with sustainable spatial planning policies to achieve a balanced relationship between economic growth, environmental conservation, and community well-being.